Factores individuales, familiares y escolares asociados a la aceptación y el rechazo social en grupos de niños escolarizados entre los 9 y 11 años de edad (2006)
This article is an advance of the study which aim is to identify individual, familiar and scholar factors associated to the acceptance and social rejection in scholar children groups between 9 and 11 years old. Two types of individual variables are considered: deficits and behavioural excesses, and the social information processing strategies. Five styles of raising are considered like familiar variables: authoritarian, permissive, careless, overprotector and democratic. In the scholar context are tree pedagogic styles: the authoritarian, the permissive and the democratic. Also is wanted to detect the perceptions that the children share on attitudes that allowed a partner as deserving to be rejected or accepted in a scholar group. To the data gathering questionnaires and semistructured interviews were designed to be applied mainly to the children. The collected information will be analyzed with corelational statistics and in some cases through content analysis. Key words: acceptance, social rejection, deficits and behavioural excesses, styles of raising, pedagogic styles, social perception.